Is a Therapeutic approach required to treat Insomnia in Pakistan? - Fatima, Laveeza; Ahmad Danial; Moosa Zulfiqar Ali (Journal of the Pakistan Medical Association, 2023)
Insomnia, defined as difficulty falling or staying asleep, is prevalent among one-third of the general population. (1) It can give rise to various physical and mental problems, such as obesity, diabetes, anxiety, and depression. (2) While there are many effective medications for insomnia, a therapeutic approach for treating it is more likely to be dependable over time. A meta-analysis exploring the benefits of cognitive behavioural therapy (CBT) for chronic insomnia revealed an improvement of sleep onset latency by 19.03 minutes, a gain of total sleep time by 7.61 minutes, and improved sleep efficiency by 9.91%. (3)CBT has been recognized as a first-line treatment for insomnia by NIH Consensus and State of the Science Statements (4)as it is equally effective as medication for a brief treatment and is more reliable over time. One in every three persons in Pakistan is reported to have sleep problems and, a third of those take sleeping pills. (5)In developing countries like Pakistan, where people don’t have resources, a therapeutic approach is likely to reduce the cost and risk of adverse effects of medications. Pakistan is a pill-oriented society, and people prefer pills over therapy. The awareness among the population to adopt treatments or shift to therapeutic interventions is close to none. The cultural stigma associated with therapy is a significant hurdle as well. Unlike medicines, therapy reduces the risk of relapse after its discontinuation. Introducing therapy in the public sector can result in more jobs for therapists and counsellors and provide a cheaper alternative to pills. The best way to introduce CBT among the population is through awareness campaigns, media, and discussions on public platforms. In addition, counsellors can provide outreach in places where additional resources are required to combat the stigma associated with psychotherapy and inform people regarding its benefits. Counsellors collaborating with other health care professionals and gaining a valuable referral source from primary care physicians can also be a meaningful strategy. It would be worth mentioning here that more studies comparing the pills to CBT should be conducted to address the issue.